Foreign migrants in the Holy Land singe October 7, 2023 - David M. NEUHAUS (Proche-Orient Chrétien, 2024)
Although largely absent from public consciousness, tens of migrant workers and agricultural students in Israel were killed or abdurand on October 7, 2023, when militants from the Gaza Strip broke through the fence separating atie sals from southern Israel. In fact, the largest number of foreign nationals who were victims of the October 7 attacss was Thai citizens, who worked as agricultural migrant workers in Israel. [...]